Technology-Dependent Optimization of FIR Filters based on Carry-Save Multiplier and 4:2 Compressor unit - Burhan Khurshid; Roohie Naaz (Electronics, 2016)
This work presents an FPGA implementation of FIR filter based on 4:2 compressor and CSA multiplier unit. The hardware realizations presented in this paper are based on the technology-dependent optimization of these individual units. The aim is to achieve an efficient mapping of these isolated units on Xilinx FPGAs. Conventional filter implementations consider only technology-independent optimizations and rely on Xilinx CAD tools to map the logic onto FPGA fabric. Very often this results in inefficient mapping. In this paper, we consider the traditional CSA-4:2 compressor based FIR filters and restructure these units to achieve improved integration levels. The technology optimized Boolean networks are then coded using instantiation based coding strategies. The Xilinx tool then uses its own optimization strategies to further optimize the networks and generate circuits with high logic densities and reduced depths. Experimental results indicate a significant improvement in performance over traditional realizations. An important property of technology-dependent optimizations is the simultaneous improvement in all the performance parameters. This is in contrast to the technology-independent optimizations where there is always an application driven trade-off between different performance parameters.